الضمانات القانونية للإستثمار الأجنبي المباشر وآثارها على دولتي الإمارات العربية المتحدة وجمهورية مصر العربية : دراسة تحليلية - جبوري، سندس حميد
This study aims at knowing and assessing the efficiency of the legal guarantees that ensure the economic growth in the United Arab Emirates (UAE) and the Arab Republic of Egypt (ARE) in light of the modern laws issued in both countries. This is because the direct and indirect foreign investments are of great concern to lots of governments, organizations, companies and individuals. Actually, the feasibility of such type of investments and the burdens and benefits entailed therein are still controversial, specially with regards to the incentives of the foreign companies in investments, the limits of such foreign investments, and the methods of organization and management in the foreign companies. The main issue of this study is to show how far the legal guarantees of the direct foreign investments are clear and sufficient, and the effect of the same in materializing direct foreign investments in both the UAE and ARE. In order to achieve the purpose of this study, the researcher has adopted the comparative practical approach in order to recognize the legal guarantees of the direct foreign investments and their effect on the UAE and ARE, to analyze such guarantee in light of the man-made laws and to activate the direct foreign investments in each of the UAE and ARE. This study has further adopted the incomplete induction method in order to analyze the legal texts related to the subject of study. The study reached a number of findings; the most important of which are that the guarantees and benefits are key to the safety and assurance of investors. This could be achieved by providing the suitable investment environment, the provision of various economic resources which shall have a prominent role in attracting and alluring investments on one hand and shall provide protection against any legislative, administrative or future procedures that the State might take or terminate if this amending the investment rules. The study recommended maintaining a high level of guarantees as enacted by the local laws for investors, expanding the same and concluding more international agreements, to ensure the continuity of economic development and the support of direct foreign investments in order to achieve the sustainable development for the State.